The creative economy in a context of transition: A review of the mechanisms of micro-resilience. (June 2015) - Andres, Lauren; Round, John
Highlights: Creative SMEs have been developing coping mechanisms to face economic downturns. Creative SMEs' micro-resiliency rests upon competitive advantages (CAs). CAs include corporate reputation, flexibility, adaptability and entrepreneurialism. Space and locality are intangible resources for creative SMEs. Creative workers' tactics and their informal networks favour micro-resiliency. Abstract: This paper assesses the coping mechanisms of creative SMEs in the context of recent economic downturns. It argues that such industries develop various forms of micro-resilience anchored in three main dimensions: production, space and people. By using the case of Digbeth and the Custard Factory as a lens to focus the discussion, it posits the argument that micro-resilience rests upon competitive advantages, including corporate reputation and the capacity of those industries to be flexible, adaptable and entrepreneurial. It also notes that space and locality, as intangible resources, act as leverages to provide an adequate working environment, allowing financial viability and clustering. Finally, it points out that creative workers and their informal networks favour a range of tactics allowing micro-resiliency.